Guidelines for treatment of umbilical and epigastric hernias from the European Hernia Society and Americas Hernia Society. Issue 3 (9th January 2020) - Henriksen, N. A.; Montgomery, A.; Kaufmann, R.; Berrevoet, F.; East, B.; Fischer, J.; Hope, W.; Klassen, D.; Lorenz, R.; Renard, Y.; Garcia Urena, M. A.; Simons, M. P.; et al.
Abstract : Background: Umbilical and epigastric hernia repairs are frequently performed surgical procedures with an expected low complication rate. Nevertheless, the optimal method of repair with best short‐ and long‐term outcomes remains debatable. The aim was to develop guidelines for the treatment of umbilical and epigastric hernias. Methods: The guideline group consisted of surgeons from Europe and North America including members from the European Hernia Society and the Americas Hernia Society. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach, the Scottish Intercollegiate Guidelines Network (SIGN) critical appraisal checklists, and the Appraisal of Guidelines for Research and Evaluation (AGREE) instrument were used. A systematic literature search was done on 1 May 2018, and updated on 1 February 2019. Results: Literature reporting specifically on umbilical and epigastric hernias was limited in quantity and quality, resulting in a majority of the recommendations being graded as weak, based on low‐quality evidence. The main recommendation was to use mesh for repair of umbilical and epigastric hernias to reduce the recurrence rate. Most umbilical and epigastric hernias may be repaired by an open approach with a preperitoneal flat mesh. A laparoscopic approach may be considered if the hernia defect is large, or if the patient has an increased risk of wound morbidity. Conclusion: This is the first European and American guideline on the treatment of umbilical and epigastric hernias. It is recommended that symptomatic umbilical and epigastric hernias are repaired by an open approach with a preperitoneal flat mesh. Abstract : This guideline evaluates the management of umbilical and epigastric hernias. How to fix them Abstract : Antecedentes: La reparación de las hernias umbilicales y epigástricas es un procedimiento quirúrgico frecuente con una tasa esperada de complicaciones baja. Sin embargo, sigue en discusión cuál es el mejor método de reparación óptimo para obtener los mejores resultados a corto y a largo plazo. El objetivo del estudio fue desarrollar una guía para el tratamiento de las hernias umbilicales y epigástricas. Métodos: El grupo para la elaboración de la guía estuvo formado por cirujanos europeos y norteamericanos junto con miembros de la European Hernia Society (EHS) y de la America's Hernia Society (AHS). Para elaborar la guía, se siguieron las recomendaciones GRADE ( Grading of Recommendations Assessment, Development and Evaluation ), SIGN ( Scottish Intercollegiate Guidelines Network ) y AGREE ( Appraisal of Guidelines for Research & Evaluation ). Se realizó una búsqueda sistemática de la literatura el 1 de mayo de 2018, que luego se actualizó el 1 de febrero de 2019. Resultados: Los trabajos dedicados de forma específica a las hernias umbilicales y epigástricas eran muy limitados en cantidad y calidad, por lo que la mayoría de las recomendaciones que se extrajeron fueron calificadas como débiles y basadas en una baja calidad de la evidencia. La recomendación principal era utilizar una malla en la reparación de las hernias umbilicales y epigástricas para reducir la tasa de recidiva. La mayoría de las hernias umbilicales y epigástricas pueden repararse mediante un abordaje abierto con una malla plana preperitoneal. Se puede considerar el abordaje laparoscópico si el defecto de la hernia es grande o si el paciente tiene un riesgo aumentado de morbilidad de la herida. Conclusión: Esta es la primera guía europea y americana del tratamiento de las hernias umbilicales y epigástricas. Se sugiere reparar las hernias sintomáticas umbilicales y epigástricas mediante un abordaje abierto con una malla plana preperitoneal.